The dismissal of John Mitford Bowker, resident agent amongst the Gqunukwebe and Mfengu at Ford Peddie,1836-39 (Historia, 2021)
-
Keywords: Gqunukwebe, J.M. Bowker; Fort Peddie; Diplomatic agent; Mfengu